2003
DOI: 10.1074/jbc.m303980200
|View full text |Cite
|
Sign up to set email alerts
|

The Host Cell Chaperone Hsp90 Is Essential for Translocation of the Binary Clostridium botulinum C2 Toxin into the Cytosol

Abstract: Clostridium botulinum C2 toxin is the prototype of the binary actin-ADP-ribosylating toxins and consists of the binding component C2II and the enzyme component C2I. The activated binding component C2IIa forms heptamers, which bind to carbohydrates on the cell surface and interact with the enzyme component C2I. This toxin complex is taken up by receptor-mediated endocytosis. In acidic endosomes, heptameric C2IIa forms pores and mediates the translocation of C2I into the cytosol. We report that the heat shock pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
151
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 132 publications
(156 citation statements)
references
References 33 publications
4
151
1
Order By: Relevance
“…This hypothesis is strengthened by our recent observation that a cellular chaperone most likely mediates translocation and/or refolding of C2I. We found that heat shock protein Hsp90 is essential for uptake of active C2I from endosomes into the cytosol of cells (32). If C2I has to become unfolded for its translocation through endosomal membranes, FIG.…”
Section: Fig 6 Ph-dependent C2i Translocation Into the Cytosol Of Vmentioning
confidence: 50%
“…This hypothesis is strengthened by our recent observation that a cellular chaperone most likely mediates translocation and/or refolding of C2I. We found that heat shock protein Hsp90 is essential for uptake of active C2I from endosomes into the cytosol of cells (32). If C2I has to become unfolded for its translocation through endosomal membranes, FIG.…”
Section: Fig 6 Ph-dependent C2i Translocation Into the Cytosol Of Vmentioning
confidence: 50%
“…In addition, growth factors such as fibroblast growth factor (FGF)-1/2 (36) and certain protein toxins like diphtheria toxin appear to use HSP90 for their translocation into cytosol in non-APC (37,38). Moreover, HSP90 was recently shown to mediate dislocation of the cholera toxin A1 (CTA1) subunit from the ER into the cytosol.…”
Section: Discussionmentioning
confidence: 99%
“…Specific inhibitors of Hsp90, such as geldanamycin or radicicol, effectively delay C2-, CDT-, or -induced cytotoxicity in various cell types by inhibiting, respectively, C2I, CDTa, or Ia entry into the cytosol. Interestingly, cytosolic entry of B. anthracis lethal toxin differs in that it is not affected by Hsp90 inhibitors (179), thereby suggesting distinct endosometo-cytosol translocation mechanisms for "A" components of this binary toxin family.…”
Section: Cell Entry and Intoxication "B" Binding To The Cellmentioning
confidence: 99%
“…4. Depiction of C2 intoxication via Hsp90, a process that is required for entry of C2I into the cytosol from acidified endosomes (179). A similar pathway is also used by toxin and CDT for intoxicating cells (178a).…”
Section: Cell Entry and Intoxication "B" Binding To The Cellmentioning
confidence: 99%